A symmetric miniature diamond anvil cell for magnetic measurements on dense hydrides in a SQUID magnetometer. Issue 4 (2nd October 2017) - Marizy, Adrien; Guigue, Bastien; Occelli, Florent; Leridon, Brigitte; Loubeyre, Paul
ABSTRACT: A new miniature diamond anvil cell was specifically designed to detect superconductivity using a SQUID (Superconducting QUantum Interference Device) magnetometer in dense hydrides directly synthesized by the reaction of hydrogen with a chemical element. The cell, made of a CuTi alloy, is fully symmetric with a very low magnetic background allowing the detection of the superconductivity of a sample as small as 3.4 × 10 4 µm 3 without background subtraction. DC measurements or AC measurements in a Magnetic Property Measurement System 3 SQUID magnetometer from Quantum Design could be performed at temperatures as low as 3 K. This high pressure cell is inserted in a modified conventional membrane diamond anvil cell to be driven for hydrogen gas loading and for fine pressure increase before magnetic measurements are performed. To synthetize and structurally characterize the superconducting sample, a 21° optical and 8.6° X-ray acceptance angle allows one to perform laser heating and X-ray diffraction at the same time. A first measurement is shown on the PdH system.